Three-dimensional morphology of the distal femur based on surgical epicondylar axis in the normal elderly population - Sato, Takashi; Mochizuki, Tomoharu (The knee, 2021)
•The distal femoral morphology was automatically calculated with high accuracy.•201 cross–sectional planes were analysed in increments of 1° from −60° to 140°.•The constant radius of sagittal curvature was 0°–80° for medial femoral condyle.•The constant radius of sagittal curvature was 0°–65° for lateral femoral condyle.•The distal femur possessed asymmetrical morphologies three-dimensionally. We aimed to analyze the surface morphology of the distal femur in three dimensions for the healthy elderly, based on the concept that the surgical epicondylar axis (SEA) is a better surrogate for the flexion–extension axis of the knee joint. We studied 77 healthy elderly volunteers (40 males and 37 females; age, 68 ± 6 years). The medial and lateral contact lines were calculated three-dimensionally, using the highest points of the medial and lateral condyles in 201 cross-sectional planes around the SEA (every 1°, −60° (hyperextension) to 140° (flexion)). A piecewise fitting function consisting of two linear segments was applied to detect the inflection point of the constant radii in the sagittal plane. The main assessment parameters were knee flexion angle at the inflection point of the radius (inflection angle), mean radius from 0° to the inflection angle (constant radius), and coronal tilt angle of the contact line. The inflection angles, constant radii, and coronal tilt angles were 78.2 ± 8.6°, 26.1 ± 2.3 mm, and −0.6 ± 3.2° and 65.6 ± 9.2°, 23.9 ± 2.2 mm, and 6.2 ± 3.2° in the medial and lateral condyles, respectively (all, P < 0.001). The coronal alignment was 88.7 ± 2.2°. The medial and lateral femoral condyles showed asymmetrical morphologies with the almost ‘constant’ radius of sagittal curvature from 0° to around 80° and 65° of knee flexion, respectively.